PssA is required for alpha-amylase secretion in Antarctic Pseudoalteromonas haloplanktis - PARRILLI, ERMENEGILDA; MARINO, GENNARO; TUTINO, MARIA LUISA; Giuliani M.; Pezzella C.; Danchin A. (Microbiology, 2010)
Extracellular protein secretion is an essential feature in bacterial physiology. The ability to efficiently secrete diverse hydrolytic enzymes represents a key nutritional strategy for all bacteria also for microorganisms living in extreme and hostile habitats, such as cold environments. However, little is known about protein secretion mechanisms occurring in psychrophilic bacteria. In this paper, the recombinant secretion of a psychrophilic alpha-amylase in the Antarctic Gram-negative Pseudoalteromonas haloplanktis TAC125 was investigated. By a combination of several molecular techniques, the function of pssA gene was related to alpha-amylase secretion in the psychrophilic bacterium. pssA gene deletion completely abolished the amylase secretion without affecting the extracellular targeting of other substrates mediated by canonical secretion systems. The pssA gene product, PssA, is a multidomain lipoprotein, predicted to be localized into the bacterial outer membrane, and displaying three TPR (Tetratrico Peptide Repeat) domains and two LysM modules. Relying on functional annotation of these domains, combined with the experimental results reported herein, we have suggested a role for PssA as a molecular adaptor, in charge of recruiting other cellular components required for specific alpha-amylase secretion. To the best of our knowledge, no proteins exhibiting the same domain organization have ever been linked to protein secretion.